Exploring Human-Nature Dynamics in Yacinta Kurniasih's Poem, Aku, Hutan Jati, dan Indonesia - Hayati, Zukhaira; Harahap, Riska Muktia Nur Aminah; Faulandi, Yusuf; Hayatullah; Purwarno, Purwarno (ITScience (Information Technology and Science), 2024)
This research aims to elucidate the underlying values and representations of nature and humanity. The study employs a qualitative approach, utilizing the hermeneutic method for interpretation and analysis. Drawing upon ecocritical perspectives, the research explores the intricate relationship between literature and the environment, highlighting the significance of literature in advocating for environmental conservation. The poem unfolds through the first-person perspective of 'Aku,' depicting their deep connection to the teak forest, which symbolizes both the physical landscape and the emotional journey of the narrator. Through vivid imagery and evocative language, the poem portrays themes of love, loss, and environmental degradation, emphasizing the profound interconnectedness between humanity and the natural world. Additionally, the portrayal of childhood innocence and imagination underscores the transformative power of curiosity, showcasing the inherent bravery and resilience of the human spirit. Moreover, the analysis delves into the cultural landscape depicted in the poem, unveiling the community's profound reverence for the environment encapsulated in their rich tapestry of myths and mystical narratives. These myths serve as potent instruments, instilling in individuals a deep sense of responsibility towards environmental stewardship. The poem masterfully weaves together the threads of human experience and environmental consciousness, inviting readers to contemplate the symbiotic relationship between humanity and nature. Through rich sensory imagery and poignant reflection, the poem celebrates the inherent beauty and richness of the natural world while urging reflection on the profound impact of human actions on the delicate balance of the ecosystem.